2010
DOI: 10.1136/jcp.2010.079905
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol based tissue fixation as an alternative for formaldehyde: influence on immunohistochemistry

Abstract: Tissues fixed in non-crosslinking alcohol based fixatives can successfully be immunohistochemically stained for most antibodies following the usual NBF based protocols. Omission of pepsin pretreatment seems to be important to retain proper morphology of immunostained tissues preserved in alcohol based fixatives. Therefore, when switching to less toxic and non-carcinogenic alcohol-based fixatives like RCL2, no major changes in the daily routine of immunohistochemistry are anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 12 publications
1
48
1
4
Order By: Relevance
“…Our results for FineFIX and RCL2 are in line with previous studies investigating the effects of both fixatives on immunohistochemical stains. 16,18,[21][22][23][24] F-Solv, on the other hand, another crosslinking but less toxic NBF substitute, would need major…”
Section: Discussionmentioning
confidence: 99%
“…Our results for FineFIX and RCL2 are in line with previous studies investigating the effects of both fixatives on immunohistochemical stains. 16,18,[21][22][23][24] F-Solv, on the other hand, another crosslinking but less toxic NBF substitute, would need major…”
Section: Discussionmentioning
confidence: 99%
“…A hypothesis was that this could be caused by the presence of epitopes that were usually masked in the native form, that were made available for antibody binding when fixation chemicals conformational changes in the protein in the different detection methods [233,234]. This theory was tested in paper I by exposing rhCEA to different chemicals and probing with anti-NCA-2 ( Figure 12), which showed that the read-out of the IFMA changed depending on the fixation chemical the recombinant protein was exposed to.…”
Section: B) Antibody Specificitymentioning
confidence: 99%
“…It leads to dermatitis and can cause irritation to the eyes. At the same time due to its carcinogenic properties it also poses a serious threat to environment (6). Despite the many advantages of formaldehyde in detecting tissues, in some cases this is unsuccessful.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the antigenic epitope by the formaldehyde solution is modified or destroyed (9). Formaldehyde cross-links molecular groups to prevent immunohistochemical reactions (6). These epitopes can be recovered with "epitope access method" (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation